The contribution of earned value analysis for cost controlling of construction projects - Shi Cia, Ng (2014)
Earned Value Analysis (EVA) is a project performance measurement technique. Managers can manage the performance of project by comparing the planned value to actual results. It allows the calculation of cost variance, performance indices and forecast the project cost performance. Therefore, EVA is very important to monitor and control the performance of the construction project. This research is using descriptive study. The purpose of this study is conducted to study the relationship between the EVA and the cost performance of the construction project. Furthermore, the aim of this study also needs to determine the effect of the EVA in the construction project. In this study, survey research will be chosen to collect the data. In order to do the survey research, questionnaire will be chosen as a quantitative method approach. There are 100 companies located in Negeri Sembilan and the sample needed is 80 companies. The results of respondent rates are 38 out of 80 companies. The results have shown that there is a positive correlation between the EVA and the cost performance of the construction project. The result of average mean also indicate that the EVA has successfully to assist the project cost within the budget is the highest mean value among the seven effects of the EVA